Databázové zdroje v chemii - Jindřich, Jindřich (Chemické listy, 2017)
The most widely used specialized chemistry databases and web services allowing access to them will be described. Besides the largest commercial three (Reaxys, SciFinder, Web of Science), some freely available services (Google Scholar, ChemSpider , PubChem, PubMed) will also be discussed. Strong and weak points of the presented databases will be emphasised and recommendations for optimal database selection and searching will be given.
Keywords: SciFinder; ChemSpider; ukládání a vyhledávání informací; chemické databáze; Databases as Topic; PubChem; Web of Science; Reaxys; databáze jako téma; Information Storage and Retrieval; Databases, Chemical; Google Scholar